GRADUATE SCHOOL STRESSORS: AN INTEGRATIVE LITERATURE REVIEW - Flaviane Cristina Rocha Cesar; Elyana Teixeira Sousa; Luana Cássia Miranda Ribeiro; Lizete Malagoni de Almeida Cavalcante Oliveira (Universidade Federal do Paraná, 2018)
Objective:To identify the scientific evidence related to the stressors faced by Master's and PhD students during their graduate program. Methodology:This was an integrative literature review conducted in October 2017 in the Virtual Library of Healthy, Web of Science, Psychology Information and PubMed databases.The review included primary articles on the topic published in English, Portuguese, and Spanish. Results:Twelve studies were analyzed, yielding three categories of stressors: personal, academic, and interpersonal relationships. Of these categories, emphasis goes to high academic workload, income, reconciling graduate studies with family and work, and the student-advisor relationship. Conclusion: The challenge for graduate students lies in reconciling the stress experienced at this time of life, academic activities, and nonacademic activities. Graduate programs need to develop high-quality scientific production that does not result in the loss of health of those involved in the process.